2005
DOI: 10.1016/s0002-9440(10)62275-4
|View full text |Cite
|
Sign up to set email alerts
|

Pro-NGF Isolated from the Human Brain Affected by Alzheimer's Disease Induces Neuronal Apoptosis Mediated by p75NTR

Abstract: The pro-form of nerve growth factor (pro-NGF) has been shown to be a high affinity ligand for p75NTR and to induce apoptosis through this receptor. It has been reported that pro-NGF, rather than mature NGF, is the predominant form of this neurotrophin in human brain. In the present work we studied the potential involvement of pro-NGF purified from human brains affected by Alzheimer's disease (AD), where it is especially abundant, in the neuronal apoptosis observed in this disease. Western blot analysis of huma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
145
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(159 citation statements)
references
References 42 publications
13
145
0
Order By: Relevance
“…Since proteolytic processing is altered in many neurological disorders (Rosenberg 2002) neurotrophic factor functions may be altered to influence disease progression. For example, increased levels of proNGF have been detected in Alzheimer's disease patients (Peng et al 2004;Pedraza et al 2005), but the cellular sources were not fully identified. Whether the abnormal proNGF secretion by astrocytes is the result of decreased protease activity or a general increase in neurotrophin synthesis requires further investigation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since proteolytic processing is altered in many neurological disorders (Rosenberg 2002) neurotrophic factor functions may be altered to influence disease progression. For example, increased levels of proNGF have been detected in Alzheimer's disease patients (Peng et al 2004;Pedraza et al 2005), but the cellular sources were not fully identified. Whether the abnormal proNGF secretion by astrocytes is the result of decreased protease activity or a general increase in neurotrophin synthesis requires further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that proneurotrophins binding to p75 mediates cell death after injury or neurodegenerative diseases such as Alzheimer's dementia (Harrington et al 2004;Peng et al 2004;Pedraza et al 2005;Volosin et al 2006). Pro-neurotrophins are produced and then cleaved by furin and other proteases to produce the mature neurotrophin (Lee et al 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Taken together, these findings suggest that high MW NGF species are abundant in the nervous system and may have their own biological activity. Some have suggested an apoptotic role for proNGF (Lee et al 2001;Beattie et al 2002;Harrington et al 2004;Pedraza et al 2005), though proNGF also has been shown to have neurotrophic activities Reinshagen et al 2000;Fahnestock et al 2004).…”
Section: Function Of Ngf and Nt-3 Protein Speciesmentioning
confidence: 99%
“…Nerve growth factor (NGF), 5 the prototypical member of the neurotrophin family of polypeptides, is essential for the survival and differentiation of central and peripheral neurons, and its role in the development and regeneration of the sympathetic and sensory nervous systems has been extensively described (1). NGF binds to the tropomyosin-related kinase A (TrkA) receptor, a tyrosine kinase receptor, and to the p75 neurotrophin receptor (p75 NTR ), a member of the tumor necrosis factor receptor family, to induce its neurotrophic effects.…”
mentioning
confidence: 99%
“…Importantly, proNGF can be secreted without being processed to mature NGF and can have its own biological effects (3). As more than just a source for NGF, proNGF was shown to induce neuronal death by apoptosis where mature NGF induced survival and differentiation (4,5). For inducing its proapoptotic effect on neurons, proNGF forms a trimeric complex with two plasma membrane receptors: p75 NTR and sortilin (4).…”
mentioning
confidence: 99%